Novel technique for locating an intruder in 3D environments by using a cooperative system of multistatic radars - Josivaldo de S. Araújo; Rodrigo M. S. de Oliveira; Carlos Leonidas da S. S. Sobrinho (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
the aim of this work is to present a new methodology, based on vector and geometrical techniques, for determining the position of an intruder in a residence (3D problem). Initially, modifications in the electromagnetic responses of the environment, caused by movements of the trespasser, are detected. It is worth mentioning that slight movements are detected by high frequency components of the used pulse. The differences between the signals (before and after any movement) are used to define a sphere and ellipsoids, which are used for estimating the position of the invader. In this work, multiple radars are used in a cooperative manner. The multiple estimates obtained are used to determine a mean position and its standard deviation, introducing the concept of sphere of estimates. The electromagnetic simulations were performed by using the FDTD method. Results were obtained for single and double floor residences.